Continuous Triboelectric Power Harvesting and Biochemical Sensing Inside Poly(vinylidene fluoride) Hollow Fibers Using Microfluidic Droplet Generation. Issue 9 (4th November 2016) - Kanik, Mehmet; Marcali, Merve; Yunusa, Muhammad; Elbuken, Caglar; Bayindir, Mehmet
Abstract : Triboelectric power harvesting and biochemical sensing inside poly(vinylidene fluoride) hollow fibers. Fiber‐based microfluidic energy harvesting system, which is also utilized as self‐powered chemical and biosensor. In vitro device concept demonstrating that triboelectric effect can be used for cell detection.